University hazing culture: challenges that remain - Akerman, Marco; Conchão, Silmara (ABCS Health Sciences, 2020)
Introduction: Hazing are trials applied to new students entering the University as a ritual of initiation. Since 2010, the research "bullying with the university" studies hazing in medical courses. This study revealed the hierarchical and power relations existing among students. Its results triggered measures adopted in a Medical School from São Paulo State, Brazil. Report: This article analyzes the changes that occurred after six years of interventions in the hazing culture. In 2015, 89 new students entering Medical School made a narrative stimulated by the question: "What did you see, live and feel related to your reception in college?”. The answers were analyzed in five thematic categories. Most have reported that there is much discomfort caused by the hazing process. They naturalized these episodes and claimed that the hierarchy in medicine supports this type of treatment. Conclusion: The hierarchical structure endorses and perpetuates the superiority condition promoted by the veteran students.